BUDIDAYA MELON MENGGUNAKAN METODE HIDROPONIK FERTIGASI TETES DI DUSUN PACUL GOWANG, JATIREJO, DIWEK JOMBANG - Yatim Ni'mah; Suprapto Suprapto; Harmami Harmami; R. Djarot; Fredy Kurniawan; Ita Ulfin; Hendro Juwono; Zeni Rahmawati; Yunia Anisa Putri; Palupi Irene Desilvia; Safira Aulia; Rajwa Abidah Sudjarwo; Ardhelia Maura Felisia (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
Pacul Gowang Hamlet is one of the hamlets located in Jatirejo Village, Diwek District, Jombang Regency. Most of the residents of this hamlet work as farmers with main commodities such as rice, corn, and vegetables. However, the farming method used is still traditional, namely planting directly in the soil, which often results in suboptimal yields. The problems faced include unproductive land, low farmer income, lack of knowledge regarding modern cultivation technology, and limited understanding of post-harvest handling and product marketing. This community service program was carried out based on a situation analysis and discussions with local farmers. The purpose is to provide a solution by introducing the hydroponic drip fertigation system, a technique of supplying nutrients through drip irrigation controlled by a timer with high precision. This system was chosen because it is more efficient in water and nutrient usage, reduces the risk of crop failure, and can be applied to limited land areas. The crop cultivated is the Sweet Net 9 melon variety, which has a high market value and stable demand, such as from supermarkets and restaurants. This activity involved 10 KKN (Community Service Program) students to utilize idle land in order to produce high-quality horticultural products, thereby increasing the income and welfare of the Pacul Gowang Hamlet community.